Alternative Media in Supporting Learning in Indonesia During The Covid-19 Pandemic - Melisa Rezi; Adam Mudinillah; Pahmi Pahmi (Jurnal Basicedu, 2022)
This study aims to determine the level of understanding of lecturers and students, especially universities in Indonesia, on the use of alternative media in the form of video conferences in supporting lectures in Indonesia in the midst of the current corona virus (covid-19) outbreak. The alternative media in question are Zoom Meet, Google Meet, Skype, Webex, and Discord, where each of these media has a different function but to achieve the same goal. Able to support lectures in Indonesia in the midst of the corona virus (covid-19) outbreak by using alternative media such as video conferencing. This study uses a descriptive qualitative approach where the meaning of the descriptive qualitative approach itself is research that uses qualitative data and then developed descriptively, this type of research is a combination of qualitative and descriptive approaches. The subjects of this study were all lecturers and students at universities in Indonesia, in which it was clear that video conferencing was widely used and played a role in supporting the learning process at the university level in Indonesia in the midst of the corona virus outbreak.